How to Read Eastern Art - Chou, Younghin (Jimoondang, 2018)
This book explains the principles underlying traditional East Asian paintings and provides a roadmap for better understanding those artworks. In the East, men of letters were the main producers and consumers of art; they equated paintings with poems that had to be deciphered. The author relies on his training as an anatomist and his extensive knowledge of Chinese classics to identify and classify recurrent subject matters and to extract their respective meanings. He translates these objects into a lexicon that can be used to communicate specific messages.